2019
DOI: 10.3390/aerospace6120126
|View full text |Cite
|
Sign up to set email alerts
|

Predesign Considerations for the DC Link Voltage Level of the CENTRELINE Fuselage Fan Drive Unit

Abstract: Electric propulsion (EP) systems offer considerably more degrees of freedom (DOFs) within the design process of aircraft compared to conventional aircraft engines. This requires large, computationally expensive design space explorations (DSE) with coupled models of the single components to incorporate interdependencies during optimization. The purpose of this paper is to exemplarily study these interdependencies of system key performance parameters (KPIs), e.g., system mass and efficiency, for a varying DC lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These comparisons revealed an accuracy of 2% to 5% for our analytical models depending on component and power level. As the modeling is similar to some of our previous work, text parts from [8,15] were re-used for the following description. Figure 3.…”
Section: Modelingmentioning
confidence: 99%
“…These comparisons revealed an accuracy of 2% to 5% for our analytical models depending on component and power level. As the modeling is similar to some of our previous work, text parts from [8,15] were re-used for the following description. Figure 3.…”
Section: Modelingmentioning
confidence: 99%
“…Such a design has potential for 10-15% power electronics size reduction over DC system, as shown by NASA convergent aeronautics solutions (CAS) study [177]. A DC power transmission system was considered in the CENTRELINE project to assess the weight and efficiency sensitivity in the electrical system both at the component level and system level with ae voltage variation between a range from 1000 V over to 5000 V [186]. The study illustrated that a high voltage level could be beneficial from overall mass and efficiency point of view.…”
mentioning
confidence: 99%
“…The serviceability limits defined by the authors could enable helicopter users to significantly reduce operating costs by extending the remaining useful life (RUL) of the engines operated in a desert environment. Finally, in the study of Biser et al [8], the possibilities of coupled, analytical models for sizing electric propulsion systems were demonstrated by considering the example of a propulsion system developed in the frame of a relevant EU-funded project. The approach proposed by the authors was found to favor model accuracy and low computational effort.…”
mentioning
confidence: 99%